2015
DOI: 10.1159/000431377
|View full text |Cite
|
Sign up to set email alerts
|

Neurohypophyseal Neuregulin 1 Is Derived from the Hypothalamus as a Potential Prolactin Modulator

Abstract: Although neuregulin 1 (Nrg1) has been identified in the rat hypothalamus, the localisation of Nrg1 in the hypothalamus-hypophyseal structure and its functions remain unclear and require further elucidation. In this study, we identified the existence of Nrg1β types I-III in the rat hypothalamus. We demonstrated that Nrg1 was partially localised in somatostatin-positive cells in the periventricular nucleus. It was also co-localised with arginine vasopressin in the supraoptic nucleus, median eminence and pituitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…These processes were accompanied by promotion in expression and secretion of PRL, which Erk inhibitor and siRNA targeting Nrg4 can suppress this process. Although a previous study has indicated the significance of the PI3K-Akt cascade in initiating PRL promoter activity, 34,35 our study found that Nrg4 concentrations below 10 nM were unable to induce phosphorylated Akt activation. Similar to Nrg1, the Erk signal is involved in the regulation of PRL expression by Nrg4.…”
Section: Discussioncontrasting
confidence: 93%
“…These processes were accompanied by promotion in expression and secretion of PRL, which Erk inhibitor and siRNA targeting Nrg4 can suppress this process. Although a previous study has indicated the significance of the PI3K-Akt cascade in initiating PRL promoter activity, 34,35 our study found that Nrg4 concentrations below 10 nM were unable to induce phosphorylated Akt activation. Similar to Nrg1, the Erk signal is involved in the regulation of PRL expression by Nrg4.…”
Section: Discussioncontrasting
confidence: 93%
“…The results of a growing number of studies suggest that NRG1 regulates cell maintenance, differentiation, proliferation, migration, and survival or apoptosis in both neuronal and nonneuronal cell types (Mei and Xiong, 2008). Research on NRGs and their corresponding receptors in both invertebrate and vertebrate models, including Drosophila (Hidalgo et al, 2001), zebrafish (Brown et al, 2017), mouse (Kato et al, 2009), rat (Zhao et al, 2015) and even non-human primate rhesus monkey (Zhao, 2013b), have shown their complex involvement in the development of the nervous system and related diseases.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The NRG1 gene is located on the 8p12 region of the short arm of chromosome 8; it can translate to six different NRG1 (neuregulin1) protein types and over 30 different isoforms that act as extracellular EGF-like ligands for ERBB3/HER3 and ERRB4/HER41; the many different isoforms may be the reason why NRG1 can influence diverse functions such as proliferation and differentiation of glial, neuronal, and Schwann cells, expression of acetylcholine receptors in synaptic vesicles during neuromuscular junction formation, growth of skeletal muscle cells, lobuloalveolar budding/milk production in the breast, differentiation of breast cancer cells, and the development of the myocardium [ 4 ]. Neurohypophyseal NRG1 is derived from the hypothalamus as a prolactin modulator and is mainly expressed in rat pituitary gonadotrope cells and possibly regulates prolactin secretion in a juxtacrine manner [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%